1997
DOI: 10.1037/0735-7036.111.4.330
|View full text |Cite
|
Sign up to set email alerts
|

Chimpanzee (Pan troglodytes) pointing: Hand shapes, accuracy, and the role of eye gaze.

Abstract: The manual pointing of 2 signing chimpanzees, Moja and Tatu, was examined in 2 experiments. Experiment 1 investigated eye-gaze direction, hand use, and hand shape while pointing. Both chimpanzees obtained the attention of a human before pointing toward an unreachable object. During 100 trials, the chimpanzees alternated their eye gaze between the object and the human while pointing. Moja's points were left-hand biased, and Tatu showed no lateral hand bias. Both indexical and whole hand points were recorded. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(102 citation statements)
references
References 32 publications
7
95
0
Order By: Relevance
“…These learned sounds included an unvoiced raspberry and also a voiced extended grunt, described as a low, loud, guttural sound made with the mouth open (also see Krauss and Fouts 1997, which noted the use of a raspberry as an attention getter by a sign-taught chimpanzee).…”
Section: Vocal Learningmentioning
confidence: 99%
“…These learned sounds included an unvoiced raspberry and also a voiced extended grunt, described as a low, loud, guttural sound made with the mouth open (also see Krauss and Fouts 1997, which noted the use of a raspberry as an attention getter by a sign-taught chimpanzee).…”
Section: Vocal Learningmentioning
confidence: 99%
“…In studies intended to determine what chimpanzees understand about the attentional states of others, investigators have typically compared the gestural and vocal behavior produced by a focal subject when an experimenter or conspecific is attending to the chimpanzee (e.g., facing the animal, making eye contact, and/ or engaging in species typical head movements) to the behavior produced when the experimenter or conspecific is not attending to the chimpanzee. Several studies have found evidence that chimpanzees differentiate between an attentive audience and an inattentive audience, such that they direct more visual gestures (e.g., species typical begging gestures made with the hand extended outward and palm oriented up) toward an individual who is oriented toward them than toward an experimenter who is oriented away from them (Hostetter et al 2001;Kaminski et al 2004;Krause and Fouts 1997;Leavens et al 2004;Liebal et al 2004;Tomasello et al 1994). …”
Section: Introductionmentioning
confidence: 99%
“…Leavens et al (2004) also found that the rate of gesture production increased when an experimenter was looking at the chimpanzees. Krause and Fouts (1997a) have shown that chimpanzees used attention-getting behaviours such as vocalisations and auditory gestures to attract the experimenter"s attention before employing pointing or other visual gestures.…”
Section: Discussionmentioning
confidence: 99%
“…have reported that the visual gestures of wild and captive gorillas were produced more often than tactile or auditory gestures when the recipient was looking at a signaller. Krause and Fouts (1997a) found that chimpanzees used attention getting behaviours such as vocalisations and auditory gestures to attract the experimenter"s attention before employing pointing or other visual gestures.…”
Section: Katja Liebal 2004mentioning
confidence: 99%
See 1 more Smart Citation